COVID-19 Versus Diabetes Mellitus: Whom Affect the Other? - Al-Rawi, Mahmood Basil A. (Asian Journal of Pharmaceutics (AJP), 2023)
Diabetes is considered as a precipitating factor for the poor outcomes of COVID-19. Patients with diabetes had a 2.5–3.9 times higher odds of being infected. Viral infection in diabetic patients could be harder to treat due to fluctuations in blood glucose levels. Their compromised immune system leads to a longer duration of recovery. Furthermore, poorly controlled diabetes impairs the immune response to viral infections. C-reactive protein, IL-6, and D-dimer are inflammatory biomarkers elevated among diabetic patients infected with COVID-19.Many scenarios could explain; how could COVID-19 induce Type 1 diabetes? and how COVID-19 brings out Type 2 diabetes? There is lack of data regarding pancreatic abnormalities and manifestation in COVID-19 patients. Hence, further investigations are required to stand on the consequences of COVID-19 in subjects with prediabetes and patients with diabetes. Losing at least 15 pounds, regular physical exercise, control diet and regular checkup are the most important measures for prevention of diabetes after COVID-19. Regular monitoring of blood sugar levels after COVID-19 illness and control of hyperglycemia as early as possible are essential to avoid development of severe complications and poor outcome. Appropriate management of comorbidities is of great significance in mitigating the COVID-19 pandemic. Diabetic patients must have priority for vaccination against COVID-19. CDC recommends that people with underlying medical conditions including diabetes should receive a third dose of COVID-19 Vaccine at least 3–6 months after completion of their second dose series.